Serum uric acid and the Five Factor Model of personality: Implications for psychopathological and medical conditions. (July 2016) - Armon, Galit
Abstract: Elevated serum uric acid (SUA) is associated with a variety of medical and psychopathological conditions. This study investigated whether elevated SUA is associated with the Five Factor Model of personality. Participants underwent a health examination at two points of time, T1 (N = 3706) and T2 (N = 2104), about 18 months apart. Ordinary least squares (OLS) regressions were used to examine the concurrent and over-18-month associations between the FFM factors and SUA levels. Extraversion was associated with elevated SUA at T1 and T2. Conscientiousness was associated with decreased SUA at T1. The associations of Extraversion and Conscientiousness with SUA decreased to marginal significance when adjusted for body weight as a possible mediator. Agreeableness was associated with decreased SUA at T1 and T2 and persisted after adjustment for covariates. A secondary analysis conducted to examine whether the FFM could predict individuals having above normal SUA levels, showed a trend similar to that observed for the OLS regressions. The associations found have direct relevance to medical and psychopathological conditions associated with elevated SUA. Highlights: The associations of personality with serum uric acid (SUA), were evaluated. Personality traits were assessed by the Five Factor Model. Personality was associated with SUA concurrently and over time. These associations might have relevance to medical and psychopathological conditions.